Scintigraphy-based analysis of possible pulmonary lesions after foam sclerotherapy: a pilot study - Lorenzo Tessari (Veins and Lymphatics, 2014)
The aims of this study were to assess extemporaneous in vivo binding between 99mTcO4- and two sclerosant detergents in foam sclerotherapy, and subsequently to control any possible damage in lungs and other organs related to sclerosant foam passage. A prospective comparative pilot study was performed on two male patients (62 and 56 years old) affected by varicose veins; each of them underwent scintigraphy investigations with free radiotracer and a scintigraphy investigation after each of the four sessions of sclerotherapy of varicose tributaries of the lower limbs with labeled sclerosant foam. One of the two patients underwent two further scintigraphic investigations, with free radiotracer and with labeled sclerosant foam, at a later stage. Four mL of 2% polidocanol (POL) foam, or four mL of 1% sodiumtetradecylsulfate (STS) foam for session were injected. The sclerosant foam was labeled with the radioactive tracer technetium pertechnetate, 99mTcO4- (120 MBq per exam). Two scintigraphy assessments for free tracer (basal) and five scintigraphy investigations of bound-tosclerosant tracer uptake/transit were obtained. No relevant variations in time/activity curves of the lungs and other organs were documented between the basal and post-sclerotherapy findings, also at the later stage. Free radiotracer mean region-of-interest data were: 336 counts (heart), 208 counts (lungs) and 371 counts (thyroid). Mean values extrapolated from each curve at each step for labeled CO2O2-based sclerosant foam were respectively: 351 counts (POL) and 328 counts (STS) for heart, 202 counts (POL) and 188 counts (STS) for lungs, 335 (POL) and 263 (STS) for thyroid. No pulmonary damage by sclerosant foam was caused. Neither immediately after treatments, nor at short-term follow-up.